HUBUNGAN PERSEPSI SISWA TENTANG PROSES PEMBELAJARAN DENGAN HASIL BELAJAR GAMBAR TEKNIK SISWA KELAS X TGB SMK N 2 PAYAKUMBUH - 2091-2094, Giva Maulani (CIVED, 2018)
Abstract—. This research to reveal the relationship of students' perceptions about the learning process with the learning outcomes of Technical Drawing Course of students of Class X TGB SMKN 2 Payakumbuh. The type of this research is a correlational descriptive research. The samples were 49 students taken by using total sampling technique. Data analysis techniques used are: 1) Descriptive analysis, 2) Analysis requirements test, consisting of normality test and linearity test, and 3) Test of Hypothesis. The result of this study showed that there is a significant relationship between students' perceptions of the learning process with the learning outcomes of Technical Drawing Courses of students of Class X TGB SMKN 2 Payakumbuh, with 95% confidence level. This can be seen from the correlation coefficient value of 0.552, means that the relationship lies in moderate category.Keywords: Student Perception, Learning Process, Learning Result